2022
DOI: 10.1186/s12864-022-08976-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and stress response analysis of cyclophilin gene family in apple (Malus × domestica)

Abstract: Background Cyclophilin (CYP) belongs to the immunophilin family and has peptidyl-prolyl cis-trans isomerase (PPIase) activity, which catalyzes the cis-trans isomerization process of proline residues. CYPs widely exist in eukaryotes and prokaryotes, and contain a conserved cyclophilin-like domain (CLD). Plant cyclophilins are widely involved in a range of biological processes including stress response, metabolic regulation, and growth and development. Result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Among all the samples from different regions of L. rotata , TFIIS and CYP95 were the most stable reference genes based on the RefFinder method. Plant cyclophilins ( CYPs ) are widely involved in a range of biological processes, including stress response, metabolic regulation, and growth and development [ 54 , 55 ]. CYP belongs to the immunophilin family and has peptidyl-prolyl cis - trans isomerase (PPIase) activity, which catalyzes the cis - trans isomerization process of proline residues.…”
Section: Discussionmentioning
confidence: 99%
“…Among all the samples from different regions of L. rotata , TFIIS and CYP95 were the most stable reference genes based on the RefFinder method. Plant cyclophilins ( CYPs ) are widely involved in a range of biological processes, including stress response, metabolic regulation, and growth and development [ 54 , 55 ]. CYP belongs to the immunophilin family and has peptidyl-prolyl cis - trans isomerase (PPIase) activity, which catalyzes the cis - trans isomerization process of proline residues.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that NRT1.1 may regulate NO 3 − -dependent Na + transport. Apples, as an important horticultural product, have significant economic benefits globally [39][40][41][42][43][44]. China has the highest apple production and nitrogen fertilizer application rates in the world.…”
Section: Introductionmentioning
confidence: 99%
“…China has the highest apple production and nitrogen fertilizer application rates in the world. Excess nitrogen fertilizer is applied to cultivated apple trees to achieve high production, but the absorption efficiency of the plant body is less than 40%, which is a large discrepancy compared to developed countries [40][41][42][43][44] and causes serious environmental problems. Furthermore, the relatively poor local climate of apple orchards in China (mainly in mountainous, rural areas), insufficient rainfall, and reduced groundwater level, as well as soil salinization caused by unreasonable irrigation and single application chemical fertilizer over a long time period, mean that the apple trees are to a large extent vulnerable to drought and salt stress, resulting in a decline in apple yield and quality.…”
Section: Introductionmentioning
confidence: 99%